Character region detection using projection profile method - Hajee Peera (2008)
This project is concerned with the extraction of character region in gray-scale images using projection profile method. It is a software project using Borland C++ to implement the algorithm and user interface (GUI) in the PC-based environment. Images to be segmented are of size limited to 600x600 pixels and are gray level.